Thinking with Whitehead and the American pragmatists : experience and reality - Henning, Brian G.; Myers, William T.; John, Joseph David (Contemporary Whitehead studies., 2015)
This collection of original essays explores the connections between the philosophies of Alfred North Whitehead and the classical American pragmatists.